Unaccompanied migrant child: victims or infringers - Abdelouahed Belattar (Revista Sobre la Infancia y la Adolescencia)
This essay is about the issue of migrant offender minors. These children are caught in the double problematic of being immigrants and being law offenders. This is a problem because of the social treatment they suffer those who have been through these kinds of situations (such as the whole migration process and the mentoring in the juvenile centers). We want to shed light on these situations explaining them briefly to know: the reality that these children face (the treatment they receive from the Minor Responsibility Law, the Law on Foreigners and the social services of the Autonomous Community of Valencia), the day-to-day problems they face and their possible consequences. The aim of this essay is to reflect on the criminality of these migrant minors and to try to prevent it